Sustainable Natural Resource Management for Future Generations: Insights from an Islamic Perspective - Akter, Taslima (Philosophy and Progress, 2025)
In the contemporary world, many environmental and social crises such as climate change, pollution, resource depletion, energy waste, deforestation, desertification, extinction of species, environmental racism, forced migration, waste trafficking, hazardous waste dumping, environmental injustice, etc. are cumulatively threatening the existence of humans and the planet itself as a result of irresponsible and immoral natural resources exploitation. Sustainable use of natural resources is a normative approach that advocates for responsible and wise use of natural resources to meet the needs of present and future generations. In Islam, the idea of sustainable use of natural resources is not new as the religious scripture Al-Quran and the Sunnah of the Prophet Mohammad (PBUH) instructed us to use the resources wisely in limits. Islam advocates for a harmonious and respectful relationship between humans and nature. Every element of the universe including humans is created by the Almighty one and only Allah in balance with a purpose. Humans are provided with everything needed to survive and flourish from nature by Allah but as vicegerent of Allah, they bear a special responsibility to take care of His creations. Islam advocates for sustainable use of natural resources so that natural resources can be distributed with justice and equity among generations and the natural equilibrium stays intact. This paper unravels the teachings of Islam regarding natural resource usage and shows how it promotes sustainable use of natural resources for future generations. In this paper, it will be shown that the Islamic perspective on natural resource usage can serve as a foundation to mitigate pollution, resource depletion, energy wastage, and other environmental crises prevailing in the current time and motivate the present generation to be cautious, moral, and responsible regarding natural resource usage. Philosophy and Progress, Vol#75-76; No#1-2; Jan-Dec 2024 P 309-334